2009
DOI: 10.1177/1010539509344112
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of College Students’ Physical Activity: Cross-Cultural Differences

Abstract: This study examined cross-cultural differences in personal and behavioral determinants of vigorous-intensity and moderate-intensity physical activity (PA) among college students living in distinctly different cultures, that is, the United States, Costa Rica, India, and South Korea. Participants of this study were recruited from randomly chosen public universities in the 4 countries during the 2006-2007 academic year. A total of 4685 students participated in the study (response rate 90%). Vigorous-intensity PA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
27
1
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 19 publications
5
27
1
1
Order By: Relevance
“…As found in a number of other studies (21)(22)(23)(24)(25)(26), female students practiced more health behaviors than male students. Among the many (25) health behavior practices studied, rates of individual health behaviors seemed to be similar to what was found in previous surveys among university students in India, e.g., 6.9% tobacco use in this study compared with 1.7%-43.6% in other studies (12)(13)(14)(15)(16)(17), 80.2% adequate physical activity [21.2%-64.8% (12,13,18,19)], 21% recommended at least five servings per day of fruits and vegetables [12% (12)], 38.6% consumption of alcohol [28.8% (12)], 3.4% illicit drug use (cannabis use) [4.5% (20)], and 50.9% normal weight in this study compared with 23.4% among physically active students (19).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…As found in a number of other studies (21)(22)(23)(24)(25)(26), female students practiced more health behaviors than male students. Among the many (25) health behavior practices studied, rates of individual health behaviors seemed to be similar to what was found in previous surveys among university students in India, e.g., 6.9% tobacco use in this study compared with 1.7%-43.6% in other studies (12)(13)(14)(15)(16)(17), 80.2% adequate physical activity [21.2%-64.8% (12,13,18,19)], 21% recommended at least five servings per day of fruits and vegetables [12% (12)], 38.6% consumption of alcohol [28.8% (12)], 3.4% illicit drug use (cannabis use) [4.5% (20)], and 50.9% normal weight in this study compared with 23.4% among physically active students (19).…”
Section: Discussionsupporting
confidence: 86%
“…A health behavior index was constructed by giving a score of 1 for each of the following 25 positive health practices and a score of 0 when the practice was not carried out (Steptoe et al, (26)): 1) current non-tobacco user, 2) occasional alcohol drinker or non-drinker, 3) moderate or high physical exercise, 4) sleeps between 7 and 8 h on average, 5) never sunbathes or uses sunscreen when sunbathing, 6) brushes teeth twice of more a day, 7) eats red meat every 2-3 days or less frequently, 8) eats five or more servings of fruits and vegetables daily, 9) eats no between-meal snacks, 10) eats breakfast almost every day, 11) does not usually add salt to meals, 12) makes a conscious effort to avoid eating foods that contain fat and cholesterol, 13) makes a conscious effort to eat foods that are high in fiber, 14) having a normal body weight (BMI = 18.5-22.9), 15) no illicit drug use in the past 12 months, 16) no gambling in the past 12 months, 17) no daily heavy Internet use (4 or more hours), 18) having had one or none sexual partner in the past 12 months, 19) not having been diagnosed with a sexually transmitted infection (STI) in their lifetime, 20) not having had a serious injury making one miss at least one full day of usual activities and/or requiring medical treatment, 21) not having been in a physical fight in the past 12 months, 22) not having carried a weapon (e.g., a gun, knife, or club) in the past month, 23) not having used any skin lightening products in the past 12 months, 24) always wearing a seatbelt when driving or seating in the front seat of a car, and 25) having dental check-up at least once a year. The Cronbach's α estimates eere positive but low (α = 0.35 for women and α = 0.24 for men), indicating considerable independence among the health practices.…”
Section: Measures Health Behavior Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike in a number of other studies (Al-Hazzaa et al, 2012b;Al Qauhiz, 2010;Banwell et al, 2009;Desai et al, 2008;Gunes et al, 2012;Kahan, 2007;Seo et al, 2009;So et al, 2012;Trujillo-Hernández et al, 2010), this study did not find that health behaviours such as physical inactivity, sedentary behaviour, frequent alcohol use and smoking were associated with overweight/obesity. It is possible that because study participants were young, in a stage of physical growth and shared similar university environment that they had similar health behaviours including physical activity patterns (So et al, 2012).…”
Section: Discussioncontrasting
confidence: 83%
“…According to Eccles, the role of peer impact also increases together with age while the impact of parents continues on the health behaviors in adolescence period (cited in Prochaska, Rodgers, & Sallis 2002). As stated in the study of Wallace et al (2000), peer support is a significant indicator for the PA of male college students but family support is a significant indicator for the PA of female college students (cited in Seo et al 2009). In the current study, the results indicated that the percentage of university students engaging in sport was higher when they had close friends engaging in sport rather than having parents doing sport.…”
Section: Jpes ®mentioning
confidence: 99%